2017
DOI: 10.21274/ls.2017.9.1.87-100
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Transition Signals in Efl Academic Writing Context: A Corpus Study

Abstract: .4). Its implication on English Language Teaching (ELT)concerning the teaching of transition signals will also be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
(3 reference statements)
1
8
0
1
Order By: Relevance
“…Regarding the frequency of CTSs, the findings were in line with Mahendra and Dewi (2017) who used their own corpus and concluded that "thus" was a dominant signal by their participants. However, investigating 146 academic expository writings, the Alshaboul et al (2013) found out that "in conclusion" occurs more frequently among other concluding terms.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Regarding the frequency of CTSs, the findings were in line with Mahendra and Dewi (2017) who used their own corpus and concluded that "thus" was a dominant signal by their participants. However, investigating 146 academic expository writings, the Alshaboul et al (2013) found out that "in conclusion" occurs more frequently among other concluding terms.…”
Section: Discussionsupporting
confidence: 80%
“…Many studies have investigated the use of transitional signals in the course of the texts (e.g., Eun & Jeon, 2009;Granger & Tyson, 1996;Hinkel, 2001;Mahendra & Dewi, 2017), but there is a dearth of research studies conducted on Concluding Transitional Signals (CTSs), especially through using corpus-based approaches on academic texts. Familiarity with these signals takes on an added importance in academic texts since learning how to write conclusions comprehensibly is a major component in an authoritative academic text.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, numerous EFL learner groups have so far been investigated. Examples include the French EFL learners (Gilquin & Granger, 2015;Granger & Tyson, 1996), the Swedish EFL learners (Tapper, 2005), Indonesian EFL learners (Mahendra & Dewi, 2017), the Brazilian EFL learners (Matte, 2017); Iranian EFL learners (Sabzevari, Haghverdi, & Bria, 2016), the Turkish EFL learners (Güneş, 2017;Uçar & Yukselir, 2017), Arab EFL learners (Al Mughrabi, 2017), and Chinese EFL learners (Milton & Tsang, 1993). An examination of the existing literature shows that African EFL learner groups, in general and Burundian EFL learner group in particular, have not been subject of investigation whatsoever.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Still another study by Mahendra and Dewi (2017) examined how Indonesian students from Ganesha University of Education used connectors in their academic writing productions with focus on errors made. Ant Conc tool was used to analyze the data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Menurut keduanya, artikel ilmiah dipublikasikan dengan harapan menginspirasi peneliti dan pengulas lain, sehingga melakukan hal yang sama dalam mengembangkan ilmu pengetahuan (Puljak & Sambunjak, 2020;Rumisek & Zemach, 2003). Tentu saja, artikel ilmiah yang baik dan menginspirasi adalah artikel yang memiliki daya kritis dan struktur argumen yang dapat diterima secara ilmiah (Eddy, 2020;Mahendra & Dewi, 2017).…”
Section: Lentera Negeriunclassified